A novel SETD2 variant causing global development delay without overgrowth in a Chinese 3-year-old boy - Wu, Yuanyuan; Liu, Fang; Wan, Ruihua; Jiao, Baoquan (Frontiers in Genetics, 2023)
Background: Luscan-Lumish syndrome is characterized by macrocephaly, postnatal overgrowth, intellectual disability (ID), developmental delay (DD), which is caused by heterozygous SETD2 (SET domain containing 2) mutations. The incidence of Luscan-Lumish syndrome is unclear. The study was conducted to provide a novel pathogenic SETD2 variant causing atypical Luscan-Lumish syndrome and review all the published SETD2 mutations and corresponding symptoms, comprehensively understanding the phenotypes and genotypes of SETD2 variantsmutations. Methods: Peripheral blood samples of the proband and his parents were collected for next-generation sequencing including whole-exome sequencing (WES), copy number variation (CNV) detection sequencing (CNV-seq) and mitochondrial DNA sequencing. Identified variant was verified by Sanger sequencing. Conservative analysis and structural analysis were performed to investigate the effect of mutation. Public databases such as PubMed, Clinvar and Human Gene Mutation Database (HGMD) were used to collect all cases with SETD2 mutations. Results: A novel pathogenic SETD2 variant (c.5835_c.5836insAGAA, p.A1946Rfs*2) was identified in a Chinses 3-year-old boy, who had speech and motor delay without overgrowth. Conservative analysis and structural analysis showed that the novel pathogenic variant would loss the conserved domains in the C-terminal region and result in loss of function of SETD2 protein. Frameshift mutations and nonsense mutations account for 68.5% of the total 51 SETD2 point mutations, suggesting that Luscan-Lumish syndrome is likely due to loss of function of SETD2. But we failed to find an association between genotype and phenotype of SETD2 mutations. Conclusions: Our findings expand the genotype-phenotype knowledge of SETD2-associated neurological disorder and provide new evidence for further genetic counselling.